Potential role of perivascular adipose tissue in modulating atherosclerosis - Ahmadieh, Samah (Clin Sci (Lond), 2020)
Perivascular adipose tissue (PVAT) directly juxtaposes the vascular adventitia and contains a distinct mixture of mature adipocytes, preadipocytes, stem cells, and inflammatory cells that communicate via adipocytokines and other signaling mediators with the nearby vessel wall to regulate vascular function. Cross-talk between perivascular adipocytes and the cells in the blood vessel wall is vital for normal vascular function and becomes perturbed in diseases such as atherosclerosis. Perivascular adipocytes surrounding coronary arteries may be primed to promote inflammation and angiogenesis, and PVAT phenotypic changes occurring in the setting of obesity, hyperlipidemia etc., are fundamentally important in determining a pathogenic versus protective role of PVAT in vascular disease. Recent discoveries have advanced our understanding of the role of perivascular adipocytes in modulating vascular function. However, their impact on cardiovascular disease (CVD), particularly in humans, is yet to be fully elucidated. This review will highlight the complex mechanisms whereby PVAT regulates atherosclerosis, with an emphasis on clinical implications of PVAT and emerging strategies for evaluation and treatment of CVD based on PVAT biology.